Artisanal and Aboriginal Subsistence Whaling in Saint Vincent and the Grenadines (Eastern Caribbean): History, Catch Characteristics, and Needs for Research and Management - Fielding, Russell; Kiszka, Jeremy J. (Frontiers in Marine Science, 2021)
Whaling has been a contentious international environmental issue for decades and carries complex ecological and socioeconomic implications. In Saint Vincent and the Grenadines (SVG), a small archipelagic nation located in the Eastern Caribbean, present-day whaling traces its origin to local interaction with American-based whalers during the nineteenth and early twentieth centuries. When American whaling in the region ceased, local shore-based whaling arose to fill the niche and to exploit the remaining, though diminished, stocks of large whales, as well as stocks of small cetaceans that the American whalers had not targeted as heavily. After a period of expansion throughout the late nineteenth and early twentieth centuries, which saw shore-whaling operations established on at least 11 islands in the region, Eastern Caribbean whaling experienced a period of attrition, during which most local whaling operations ceased. Two operations, both based in SVG, continue regularly today. This paper reviews the past and present status of whaling activities in SVG from the literature and using recent data collected from 2007 to 2017 through logbook data, interview surveys, and ethnographic observations. Small cetacean captures have been documented since 1949, and at least 15 species of odontocetes have been captured (primarily delphinids). From 1949 to 2017, a total of 13,856 small cetacean captures has been recorded, including 5,896 short-finned pilot whales (Globicephala macrorhynchus), 109 killer whales (Orcinus orca), and 7,851 other small cetaceans. Small cetacean catch records are largely incomplete and total catch estimates could not be attempted. Reliable abundance estimates do not exist. Consistent records for the take of large whales are only available for the period 1986–2020, during which 45 humpback whales (Megaptera novaeangliae) and 2 Bryde’s whales (Balaenoptera edeni) were taken. Additionally, 8 sperm whale (Physeter macrocephalus) captures were reported from 1967 and 1974. We also review whaling practices, existing national policy on whaling, management techniques outside of formal policy regimes, research needs, and future management perspectives. Future monitoring and management of whaling activities in SVG are strongly needed to assess the sustainability of small cetacean exploitation.